Establishment of neural circuits during zebrafish development: characterization and optimization of imaging conditions - Viegas, Mariana Bray (2020)
Tese de mestrado, Biologia Evolutiva e do Desenvolvimento, Universidade de Lisboa, Faculdade de Ciências, 2020